Revealing Spanish mackerel’s diversity in Indonesian through local commodities in the fish market (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Widayanti R, Nugroho HA, Megarani DV, Widiasih DA, Pakpahan S. 2021. Revealing Spanish mackerel’s diversity in Indonesian through local commodities in the fish market. Biodiversitas 23: 624-630. The objective of this study was to explore the diversity of Spanish mackerel in Indonesian Archipelago based on commodities offered in local fish markets. Eighteen specimens were collected from six different fish markets around the Indonesian archipelago. According to Wallace Line, the cytochrome B sequence was used as a genetic marker to reveal diversity from West Indonesia to East Indonesia. Gene amplification was performed using the polymerase chain reaction followed by Sanger sequencing. Based on DNA sequence analysis, we identified three species of Spanish Mackerel available at various fish markets around the region. The first group is related to Scomberomorus commerson, which was sold in both Western and Eastern Indonesian fish markets; the second group is related to Scomberomorus semifasciatus, which was sold in Eastern Indonesian fish markets; and the third group is related to Scomberomorus koreanus, which was sold in Western Indonesian fish markets. The genetic differences amongst Spanish Mackerel populations ranged from 0 to 17% and the average evolutionary divergence in the overall populations was determined to be 4%. The data collected can be utilized to initiate map mackerel diversity based on CYT B sequence throughout the Indonesian Archipelago, as well as for further study and application in the identification of foods produced from mackerel.